Analisis Efektivitas Sistem Informasi Akuntansi Penggajian dalam Mendukung Pengendalian Intern Pada PT. Kereta Api Indonesia (Persero) UPT. Balai Yasa Pulubrayan - Yafika Apriliza; Kamilah K; Atika (Universitas Muhammadiyah Surabaya, 2023)
This research aims to analyze the accounting, payroll and internal control information systems at PT. Indonesian Railways (Persero) UPT. Balai Yasa Pulubrayan which is located on Jl. Ps., Pulo Brayan Bengkel, Kec. Medan Tim., Medan City, North Sumatra 20241. The method used in this research is a qualitative method with a descriptive approach, data is collected by observation, interviews and documentation. The research results show that the accounting information system at PT. Indonesian Railways (Persero) UPT. Balai Yasa Pulu Brayan has been running quite well and effectively, the company has implemented a computerized system and has shown the division of duties and responsibilities for each section within the company, recording procedures and documents that are sufficient to support the implementation of each procedure included in the control internal. Payroll accounting information system at PT. Indonesian Railways (Persero) UPT. Balai Yasa Pulubrayan has fully supported the elements of internal control related to payroll. Because it has shown responsibility to the authorities therein. Payroll Accounting System implemented by PT. Indonesian Railways (Persero) UPT. Balai Yasa Pulubrayan is in accordance with the Islamic economic perspective and is in accordance with what was recommended by the Prophet, Islamic values have been fulfilled because employee salaries have been given fairly and appropriately according to the position of each employee. Keywords: Accounting Information Systems, Payroll, Internal Control